Le néo-réalisme ou la formulation du paradigme hégémonique en relations internationales - Rioux, Jean-François; Keenes, Ernie; Légaré, Gregg (Études internationales, 1988)
This article provides an analytical framework which we employ to examine the 'interparadigm debate' currently underway in the field of international relations. Arguing that this debate is more significant than the previous 'grand debates' in the field because it is simultaneously fought on the terrains of ontology, epistemology and values, we use these categories to examine the central propositions of the major paradigms of international relations. We argue that the interparadigm debate is a series of attacks on realism from the other perspectives, which neo-realists attempt to counter by a reconstruction of realism through the appropriation and reinterpretation of concepts and arguments used by its main critics. The refurbishment of realism corresponds to an attempt at maintaining the intellectual hegemony of the paradigm on the teaching and practice of world politics. We think that the hegemonic synthesis under the auspices of realism is not desirable and constitutes a retrograde move which ought to be resisted by scholars seeking a more relevant and less 'americanized' discipline of international relations.